Latitudinal patterns and their climate drivers of the δ13C, δ15N, δ34S isotope signatures of Spartina alterniflora across plant life-death status: a global analysis - Zhang, Dongjie; Wang, Hui; Liu, Xuepeng; Ao, Kang; He, Wenjun; Wang, Tongxin; Zhang, Mingye; Tong, Shouzheng (Frontiers in Plant Science, 2024)
Isotopic signatures offer new methods, approaches, and perspectives for exploring the ecological adaptability and functions of plants. We examined pattern differences in the isotopic signatures (δ 13 C, δ 15 N, δ 34 S) of Spartina alterniflora across varying plant life-death status along geographic clines. We extracted 539 sets of isotopic data from 57 publications covering 267 sites across a latitude range of over 23.8° along coastal wetlands. Responses of isotopic signatures to climate drivers (MAT and MAP) and the internal relationships between isotopic signatures were also detected. Results showed that the δ 13 C, δ 15 N, and δ 34 S of S. alterniflora were -13.52±0.83‰, 6.16±0.14‰, and 4.01±6.96‰, with a range of -17.44‰ to -11.00‰, -2.40‰ to 15.30‰, and -9.60‰ to 15.80‰, respectively. The latitudinal patterns of δ 13 C, δ 15 N, and δ 34 S in S. alterniflora were shaped as a convex curve, a concave curve, and an increasing straight line, respectively. A decreasing straight line for δ 13 C within the ranges of MAT was identified under plant life status.Plant life-death status shaped two nearly parallel decreasing straight lines for δ 34 S in response to MAT, resulting in a concave curve of δ 34 S for live S. alterniflora in response to MAP. The δ 15 N of S. alterniflora significantly decreased with increasing δ 13 C of S. alterniflora, except for plant death status. The δ 13 C, δ 15 N, and δ 34 S of S. alterniflora are consistent with plant height, stem diameter, leaf traits, etc, showing general latitudinal patterns closely related to MAT. Plant lifedeath status altered the δ 15 N (live: 6.55±2.23‰; dead: -2.76±2.72‰), latitudinal patterns of S. alterniflora and their responses to MAT, demonstrating strong ecological plasticity and adaptability across the geographic clines. The findings help in understanding the responses of latitudinal patterns of the δ 13 C, δ 15 N, and δ 34 S isotope signatures of S. alterniflora in response plant life-death status, and provide evidence of robust ecological plasticity and adaptability across geographic clines.